VHDLISTE: An Instructional Strategy to Cover the Additional Content beyond the Curriculum - Pujar, Anita M; Dol, Sunita M (Journal of Engineering Education Transformations, 2025)
In current scenario of engineering education, Students must have more practical knowledge and skills required to work in the technologies that are currently used in industries though they are not the part of the curriculum. The instruction based videos help students to develop their hands on the new skills that are essential for their adaptability to new technologies. Handout is the guided document which contains the instructions to follow during the laboratory session to complete the problem statement given in the assignment. Assessment of their knowledge acquirement and skills is done through grading of assignments given to them. So in this article, VHDLISTE (Instructional Videos followed by Handout Learning – Implement, Submit, Test, and Evaluate) instructional strategy is designed and implemented for Tableau: A Visual Data Analytics Tool which is the part of the course Business Intelligence and Big Data Analytics of Final Year Computer Science and Engineering but is not covered in the syllabus. This VHDLISTE instructional strategy consists of six phases V- Instructional Videos, HDL- Handout Learning, I – Implement, S – Submit, T-Test, and E – Evaluate. In first phase V - Instructional Videos phase, students watch the instructional videos prepared by the instructor to get acquainted with the Tableau tool. In second phase HDL, students go through the lab handouts to read the instructions given for completing the lab assignment. In I – Implement phase, students implement the problem statement related to Tableau tool while test on covered topics is conducted in T-Test phase. In S – Submit, students submit the problem statement on institutional MOODLE. Instructor conducts the test on covered topic in T-Test phase. Instructor evaluates the problem statement as well as test submitted by students on institutional MOODLE in E – Evaluate phase. Learning objective (LOs) of this study is to teach the problem analysing and solving ability. These LOs are 1) Apply Filters on Dimensions and Measures for given dataset using Tableau (LO1) and 2) Apply K-means Clustering on given dataset in Tableau (LO2). The research question is - Whether the use of instructional strategy VHDLISTE is useful for learning the content beyond the curriculum? This activity is conducted for two Academic Years 2020-21, 2021-22 and 2022-23. The result of applying this strategy and perception of students are also explained. The result showed that this strategy improves the problem analysis as well as problem solving ability of students. Using t-test statistical analysis, it is found that there is significant difference in mean score between sample and overall population means for LO1 as well as LO2 for all these three years.